2019
DOI: 10.1093/advances/nmy118
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins of Natural Origin: Molecular Mechanisms and Implications for Lipid Disorder and Aging-Associated Diseases

Abstract: Proanthocyanidins are phytonutrients formed by oligomerization or polymerization of subunits catechin, epicatechin, and their gallic acid esters. Proanthocyanidins are a component of many plants and thus form an integral part of the human diet. Oligomeric proanthocyanidins are currently marketed as medicinal products that target vascular disorders and chronic pathological conditions, many of which are age-associated. Proanthocyanidins are also characterized by their effects on energy homeostasis. Not dissimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 113 publications
1
36
0
Order By: Relevance
“…Among bioactive components in the cranberries, PAC (condensed tannins) might be one of the promising candidates eliciting the lipid lowering effect. Nie & Sturzenbaum (25) reviewed the impact of PAC of natural origin on lipid metabolism in the literature. They indicated that PAC from different food sources could modulate blood lipids through a variety of molecular mechanisms, including restriction of lipid absorption, coordination of digestion of neutral lipids, inhibition of lipase, stimulation of β-oxidation and reduction of liver de novo lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among bioactive components in the cranberries, PAC (condensed tannins) might be one of the promising candidates eliciting the lipid lowering effect. Nie & Sturzenbaum (25) reviewed the impact of PAC of natural origin on lipid metabolism in the literature. They indicated that PAC from different food sources could modulate blood lipids through a variety of molecular mechanisms, including restriction of lipid absorption, coordination of digestion of neutral lipids, inhibition of lipase, stimulation of β-oxidation and reduction of liver de novo lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Proanthocyanidins (PACs), known as condensed tannins, are found in a wide variety of fruits (e.g., berries), in addition to grapes, and other sources such as flowers, seeds of some plants, nuts or barks [80,81]. Plant and food-derived PACs are also attracting attention due to their ability to prevent chronic diseases [82]. For example, PACs from grape seeds and blackberry-blueberry fermented beverages have shown high anti-inflammatory and antioxidant activity in vitro [83] and have shown a broad therapeutic health effect against diabetes mellitus and obesity.…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…Over the last decade, plant and food-derived PACs are attracting attention not only from the food industry but also from public health organizations due to their ability to prevent chronic diseases [5,6,7]. As examples of the effect of PACs from different matrices is not difficult to find studies regarding juices, syrup and extract cranberry-derived PACs which demonstrated to be effective in the prevention of urinary tract infection in vivo and in vitro [8,9,10]; proanthocyanidins from blueberry-blackberry fermented beverages that showed high antioxidant and anti-inflammatory activity in vitro [11]; or PACs from a persimmon leaf tea that suggested their antihypertensive effect in animal models [12].…”
Section: Introductionmentioning
confidence: 99%